2022
DOI: 10.26434/chemrxiv-2022-3f8zm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Chiral Macrocycle for the Synthesis of Both Mechanically Planar Chiral Rotaxanes and Catenanes in Excellent Enantiopurity

Abstract: Active-template auxiliary methodologies have previously been developed for the stereoselective synthesis of chiral interlocked molecules in which the mechanical bond provides the sole stereogenic unit. To date however, the covalent auxiliary has been included in the half-axle components (rotaxanes) or pre-macrocycle components (catenanes), and thus mechanically chiral rotaxane and catenane syntheses rely on different chiral components. Here we present a single, simple amino acid-derived macrocycle that mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Catenane 3 was synthesized (Fig. 2a) using an active template 17 Cu-mediated alkyne-azide cycloaddition reaction between azide/alkyne pre-macrocycle alkene (Z)-1 and chiral bipyridine macrocycle (S)-2 (98% ee) 18 . 1 H NMR analysis confirmed that catenane 3 was isolated as a single diastereomer (>96% de), consistent with the covalent stereochemistry of (S)-2 efficiently controlling the relative orientation of the bipyridine and alkene containing macrocycles 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catenane 3 was synthesized (Fig. 2a) using an active template 17 Cu-mediated alkyne-azide cycloaddition reaction between azide/alkyne pre-macrocycle alkene (Z)-1 and chiral bipyridine macrocycle (S)-2 (98% ee) 18 . 1 H NMR analysis confirmed that catenane 3 was isolated as a single diastereomer (>96% de), consistent with the covalent stereochemistry of (S)-2 efficiently controlling the relative orientation of the bipyridine and alkene containing macrocycles 18 .…”
Section: Resultsmentioning
confidence: 99%
“…2a) using an active template 17 Cu-mediated alkyne-azide cycloaddition reaction between azide/alkyne pre-macrocycle alkene (Z)-1 and chiral bipyridine macrocycle (S)-2 (98% ee) 18 . 1 H NMR analysis confirmed that catenane 3 was isolated as a single diastereomer (>96% de), consistent with the covalent stereochemistry of (S)-2 efficiently controlling the relative orientation of the bipyridine and alkene containing macrocycles 18 . Catenane 3 also contains a coconformational geometric stereogenic unit 19 , the configuration, Eco-c, of which is controlled by the geometry of the starting pre-macrocycle, (Z)-1, and fixed in the interlocked product due to the steric bulk of the styrene and silyl ether units which prevent shuttling of the bipyridine macrocycle between the two triazole-containing compartments.…”
Section: Resultsmentioning
confidence: 99%
“…Catenane 3 was synthesized (Fig. 2a) using an active template 29 Cu-mediated alkyne-azide cycloaddition reaction between azide/alkyne pre-macrocycle alkene (Z)-1 and chiral bipyridine macrocycle (S)-2 (98% ee) 30 . 1 H NMR analysis confirmed that catenane 3 was isolated as a single diastereomer (>96% de), consistent with the covalent stereochemistry of (S)-2 efficiently controlling the relative orientation of the bipyridine and alkene containing macrocycles 30 .…”
Section: Resultsmentioning
confidence: 99%
“…2a) using an active template 29 Cu-mediated alkyne-azide cycloaddition reaction between azide/alkyne pre-macrocycle alkene (Z)-1 and chiral bipyridine macrocycle (S)-2 (98% ee) 30 . 1 H NMR analysis confirmed that catenane 3 was isolated as a single diastereomer (>96% de), consistent with the covalent stereochemistry of (S)-2 efficiently controlling the relative orientation of the bipyridine and alkene containing macrocycles 30 . Catenane 3 also contains a coconformational geometric stereogenic unit 31 , the configuration, Eco-c, of which is controlled by the geometry of the starting pre-macrocycle, (Z)-1, and fixed in the interlocked product due to the steric bulk of the styrene and silyl ether units which prevent shuttling of the bipyridine macrocycle between the two triazole-containing compartments.…”
Section: Resultsmentioning
confidence: 99%